2019
DOI: 10.3390/ijerph16030412
|View full text |Cite
|
Sign up to set email alerts
|

Medication Event Monitoring System for Infectious Tuberculosis Treatment in Morocco: A Retrospective Cohort Study

Abstract: Non-adherence to tuberculosis (TB) treatment is a barrier to effective TB control. We investigated the effectiveness of a Medication Event Monitoring System (MEMS) as a tailored adherence-promoting intervention in Morocco. We compared patients who received a MEMS (n = 206) with patients who received standard TB care (n = 141) among new active TB patients with sputum smear-positive. The mean total medication days were 141.87 ± 29.5 in the control group and 140.85 ± 17.9 in the MEMS group (p = 0.7147), and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
1
25
2
1
Order By: Relevance
“…The new TB patients may have stronger confidence and determination to cure the disease which facilitate them to take anti-tuberculosis medicine in time and quantity; however, the relapse patients may hold the idea that the disease would recur even it is cured temporarily and they may also require more complicated treatment, so they could take medicine not seriously. 33,34 In a previous study, medication duration was significantly negatively associated with medication adherence, 35 but the association in our study was not significant (p=0.090), which may be due to regional differences. Additionally, the number of anti-TB drugs patients took and whether they only took free anti-TB drugs were not associated with medication adherence.…”
Section: Discussioncontrasting
confidence: 89%
“…The new TB patients may have stronger confidence and determination to cure the disease which facilitate them to take anti-tuberculosis medicine in time and quantity; however, the relapse patients may hold the idea that the disease would recur even it is cured temporarily and they may also require more complicated treatment, so they could take medicine not seriously. 33,34 In a previous study, medication duration was significantly negatively associated with medication adherence, 35 but the association in our study was not significant (p=0.090), which may be due to regional differences. Additionally, the number of anti-TB drugs patients took and whether they only took free anti-TB drugs were not associated with medication adherence.…”
Section: Discussioncontrasting
confidence: 89%
“…Meanwhile, our findings are in contrast to the study from Morocco and South African. In rural Morocco, a medication event monitoring system with SAT increased treatment success and decreased the loss to follow-up among people with new smear positive pulmonary TB when compared to SAT alone, but only age, sex and health facility were adjusted for while deriving the adjusted measures of association [ 12 ]. Another study in South Africa, using SIMpill system (real time data communication with a web-based application by SMS every time the patient opens the bottle) also found that TB cure rates improved compared with control group, but the study did not describe the management approach of control group, and only 24 people were involved in the EMM group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAT alone, but only age, sex and health facility were adjusted for while deriving the adjusted measures of association [12]. Another study in South Africa, using SIMpill system (real time data communication with a web-based application by SMS every time the patient opens the bottle) also found that TB cure rates improved compared with control group, but the study did not describe the management approach of control group, and only 24 people were involved in the EMM group [19].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with other EMM studies that provided real-time data. In rural Morocco, EMM (that provide a real-time data) increased treatment success and decreased the lost to follow-up among people with new smear positive pulmonary TB when compared to SAT alone [20]. Another study in South Africa, using SIMpill system (real-time data communicated with a web-based application by SMS every time the patient opens the bottle), also found that TB cure rates improved compared with the control group.…”
Section: Interpretation Of Key Findingsmentioning
confidence: 96%